Viabilidade econômica da implantação de uma planta de fertilizantes - Marioto Filho, Jaime Aparecido (2018)
With the technological advancement and great growth on agriculture in recent years, big national company’s e producers need to invest to continue in front of the global market of agriculture inputs. With this in mind, looking for a differential that seeks to increase the quantity of pounds per hectare and reduce direct and indirect costs of harvesting is necessary. Based on this, the following work aims to propose scenarios and evaluate the critical methods of investment analysis to know in which scenarios will be feasible an implementation of a fertilizer factory in one of the regions that most produce agricultural inputs in Brazil. A bibliographic study allowed to identify as variables and tools that are fundamental for the resolution of the proposed problem. A research that is practical provides, in addition to the use of MS Excel and investment analysis equations, an application of an interview with people who have experience and knowledge to find information that will support the decision making. The positive results that has been obtained with the research have shown that the contribution margin of the Project is high and the investment is quite viable, even in lower taxes of operation and may help other studies or investment decision in that área.